Massive Amniotic Fluid Aspiration in a Case of Sudden Neonatal Death With Severe Hypoplasia of the Retrotrapezoid/Parafacial Respiratory Group - Lavezzi, Anna M.; Poloniato, Antonella; Rovelli, Rosanna; Lorioli, Laura; Iasi, Gabriela Alejandra; Pusiol, Teresa; Barera, Graziano; Ferrero, Stefano (Frontiers in Pediatrics, 2019)
We report a case of a baby, who, after pregnancy complicated by maternal Addison's disease and Hashimoto's thyroiditis and natural delivery, unexpectedly presented a cardiorespiratory collapse and died 1 hour after birth without responding to prolonged neonatal resuscitation maneuvers. The cause of death was reliably established by carrying out a forensic postmortem examination. More specifically, the histological examination of the lungs showed the presence of abundant endoalveolar and endobronchial cornea scales caused by absorption of amniotic fluid. The neuropathological examination of the brainstem highlighted severe hypodevelopment of the retrotrapezoid/parafacial respiratory group, which is a complex of neurons located in the caudal pons that is involved in respiratory rhythm coordination, especially expiration, in conditions of enhanced respiratory drive, as well as in chemoreception. This neuropathological finding shed new light on the mechanisms underlying the massive amniotic fluid aspiration which led to this early death.